Lagged Dividend, Profit Growth, And Company Growth On Dividend Policy With Capital Structure As The Moderation Variable - Riri Mayliza; Nanda Suryadi (International Journal of Economics Development Research (IJEDR), 2023)
Investors will see dividends as a signal about a company's future prospects. The purpose of this study is to see the influence of Lagged Dividend, Profit Growth, and Company Growth on Dividend Policy and how the Capital Structure affects the relationship between independent variables and dependent variables in banking industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research used the PLS (Partial Least Square) analysis method with software, namely the SmartPLS 2.0 application. The results that have been obtained in the form of the variable Lagged Dividend (X1) have a positive and also significant influence on Dividend Policy, Profit Growth (X2) has a negative and also significant influence on Dividend Policy, Company Growth has a positive and also significant influence on Dividend Policy. Capital Structure manages to moderate the relationship between lagged dividends and dividend policy. The capital structure failed to moderate the relationship of profit growth and company growth to dividend policy. This study obtained an Adjusted R-Square result of 0.526 which describes the variables Lagged Dividend, Profit Growth, Company Growth, and Capital Structure as moderation variables with an effect of 52.6%, then the remaining 47.4% is influenced by variables that are not discussed in this study.